1996
DOI: 10.1111/j.1469-8137.1996.tb04370.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerial dispersal of lichen soredia in the maritime Antarctic

Abstract: SUMMARYAn aerobiological monitoring programme was carried out for over a year on Signy Island, South Orkney Islands, Antarctica. Collections were made using arrays of rotorod samplers at three sites. Lichen soredia were found to be the most abundant air borne propagules, more so than ascospores, the sexual propagules of lichen fungi. The dominance of soredia over ascospores appeared to decrease with increasing maturity of fellfield sites. No correlations were found with temperature, relative humidity or wind s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 27 publications
3
64
0
Order By: Relevance
“…Therefore lichen-derived IN, when airborne, are candidiates for initiating ice formation leading to precipitation. In an aerobiological monitoring programme carried out on Signy Island in the Maritime Antarctic, lichen soredia (an asexual reproductive unit composed of algae or cyanobacteria surrounded by fungal hyphae) were the most abundant airborne propagules with a size range of 30 to 100 µm (Marshall 1996). Tormo et al (2001) also found lichen soredia in urban air in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore lichen-derived IN, when airborne, are candidiates for initiating ice formation leading to precipitation. In an aerobiological monitoring programme carried out on Signy Island in the Maritime Antarctic, lichen soredia (an asexual reproductive unit composed of algae or cyanobacteria surrounded by fungal hyphae) were the most abundant airborne propagules with a size range of 30 to 100 µm (Marshall 1996). Tormo et al (2001) also found lichen soredia in urban air in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Henderson-Begg et al (2009) suggested that canopy lichen biomass in temperate forest is similar to leaf biomass. Lichen detection directly in air has been pursued by Marshall (1996) in an aerobiological monitoring programme, where he found lichen soredia to be the most abundant airborne propagule with a size range of 30Á100 mm on Signy Island in Maritime Antarctica.…”
Section: Biological Crusts and Lichensmentioning
confidence: 99%
“…Lichens face considerable problems in colonising new sites and maintaining existing populations. Mycobionts can distribute separately via Asco-or Basidiospores, or asexual by singular lichen structures, that contain both, mycobiont and phycobiont, such as insidia (protuberances from the thallus of corticated algae and medullary tissue), soredia (several algal cells encased by a hyphae) or hormocrusts (fragments if filamentous cyanophyte Nostoc spp with hypha penetrating the thallus fragments (Marshall, 1996;Oksanen, 2006)). …”
Section: Biological Crusts and Lichensmentioning
confidence: 99%
“…However, dispersal by water is more probable (Coulson et al 2002), but has not been investigated in Antarctic springtails other than on a very local scale (Hayward et al 2004). The low tolerance of desiccation by springtails sets them apart from many other Antarctic organisms for which wind is a significant agent of dispersal (Marshall 1996(Marshall , 1997Marshall & Chalmers 1997;Marshall & Convey 1997;Muñ oz et al 2004).…”
Section: Introductionmentioning
confidence: 99%